Ras il-Wardija sanctuary revisited : a re-assessment of the evidence and newly informed interpretations of a Punic-Roman sanctuary in Gozo (Malta) - Azzopardi, George, (Archaeopress Publishing Ltd, 2017)
The secluded sanctuary on the coastal promontory of Ras il-Wardija on the central Mediterranean island of Gozo (near Malta) constitutes another landmark on the religious map of the ancient Mediterranean. Ritual activity at the sanctuary seems to be evidenced from around the 3rd century BC to the 2nd century AD and, possibly, even as late as the 4th century AD. This ritual activity was focused in a small built temple and in a rock-cut cave that seems to have incorporated a built extension in a later stage. This text examines the significance of the site.